CAN LEARNINGAPPS.ORG ENHANCE STUDENTS’ TOEFL STRUCTURE SCORE? : FOCUSING ON SELF ASSESSMENT - Faridatul Istighfaroh (Premise: Journal of English Education and Applied Linguistics, 2023)
Due to lack of study numbers on learning media for TOEFL score betterment, the purpose of this study is to outline the improvement of TOEFL score, particularly in section two or structure and written expression part after using learningapps.org as a learning aid. Data were statistically analyzed by using quantitative methodology. The 26 students participated in this study and the result of the study reveals that there is a negative relation between learningapps.org as learning media on students’ comprehension of the structure and written expression TOEFL test with a significant value of 0.05.